Effect of schistosomiasis and soil-transmitted helminth infections on physical fitness of school children in Côte d'Ivoire. - Ivan Müller; Jean T Coulibaly; Thomas Fürst; Stefanie Knopp; Jan Hattendorf; Stefanie J Krauth; Katarina Stete; Aurélie A Righetti; Dominik Glinz; Adrien K Yao; Uwe Pühse; Eliézer K N'goran; et al. (PLoS Neglected Tropical Diseases)
Background Schistosomiasis and soil-transmitted helminthiasis are important public health problems in sub-Saharan Africa causing malnutrition, anemia, and retardation of physical and cognitive development. However, the effect of these diseases on physical fitness remains to be determined. Methodology We investigated the relationship between schistosomiasis, soil-transmitted helminthiasis and physical performance of children, controlling for potential confounding of Plasmodium spp. infections and environmental parameters (i.e., ambient air temperature and humidity). A cross-sectional survey was carried out among 156 school children aged 7-15 years from Côte d'Ivoire. Each child had two stool and two urine samples examined for helminth eggs by microscopy. Additionally, children underwent a clinical examination, were tested for Plasmodium spp. infection with a rapid diagnostic test, and performed a maximal multistage 20 m shuttle run test to assess their maximal oxygen uptake (VO(2) max) as a proxy for physical fitness. Principal findings The prevalence of Schistosoma haematobium, Plasmodium spp., Schistosoma mansoni, hookworm and Ascaris lumbricoides infections was 85.3%, 71.2%, 53.8%, 13.5% and 1.3%, respectively. Children with single, dual, triple, quadruple and quintuple species infections showed VO(2) max of 52.7, 53.1, 52.2, 52.6 and 55.6 ml kg(-1) min(-1), respectively. The VO(2) max of children with no parasite infections was 53.5 ml kg(-1) min(-1). No statistically significant difference was detected between any groups. Multivariable analysis revealed that VO(2) max was influenced by sex (reference: female, coef. = 4.02, p<0.001) and age (years, coef. = -1.23, p<0.001), but not by helminth infection and intensity, Plasmodium spp. infection, and environmental parameters. Conclusion/significance School-aged children in Côte d'Ivoire showed good physical fitness, irrespective of their helminth infection status. Future studies on children's physical fitness in settings where helminthiasis and malaria co-exist should include pre- and post-intervention evaluations and the measurement of hemoglobin and hematocrit levels and nutritional parameters as potential co-factors to determine whether interventions further improve upon fitness.